Evaluasi Pembinaan Pegawai di Lingkungan Kantor Pencarian dan Pertolongan Palembang - Sukamto, Sukamto; Lisdiana, Lisdiana; Berlian, Ong (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2025)
The purpose of this research is to evaluate employee development within the Palembang Search and Rescue Office. Evaluation of employee development in the Palembang Search and Rescue Office environment is qualitative research. Data or information is collected through interviews with informants, observation and documentation. The research results show the importance of employee development. Research shows that employee development at the Palembang Search and Rescue Office has a crucial role in improving employee skills, knowledge and preparedness. Guidance is an important factor in dealing with emergency situations and involving competent parties in search and rescue operations. Facilities and infrastructure for employee coaching are identified as key elements in providing effective coaching. Training rooms, simulations and other supporting equipment make a positive contribution to the development of operational skills. Employee welfare, including accommodation facilities, health facilities and recreation areas, is also recognized as an important factor in supporting coaching effectiveness. Good physical and mental condition contributes to employee readiness in carrying out their duties. The process of regular evaluation and feedback on employee performance helps identify strengths and weaknesses. Using evaluation results as a basis for further improvement and development is a determining factor in the success of employee development.